Bioethanol production from acidic and enzymatic hydrolysates of mixed microalgae culture. (15th July 2017) - Shokrkar, Hanieh; Ebrahimi, Sirous; Zamani, Mehdi
Graphical abstract: Highlights: Reducing sugars extraction from mixed culture of microalgae via different pre-treatment strategies. The effects of MgSO4 and CaCl2 as lewis acid in acidic pretreatment on sugar yield. Comparison of the reducing sugar yield of dried and wet microalgae using enzymatic hydrolysis. Comparison of bioethanol yield of the fermentable sugars derived from different pre-treatment procedures. Abstract: Mixed microalgae cultures are considered as an attractive research area compared to traditional pure culture to dominate cultivation contamination risk and enhance economic feasibility of large-scale biofuel production. However, pre-treatment and bioethanol production from mixed microalgae culture has not been reported yet. Therefore, this study was aimed to evaluate the effect of different pre-treatment strategies including acidic, alkaline, and enzymatic hydrolysis on the sugar extraction from mixed microalgae. Besides, the effects of MgSO4 and CaCl2 as lewis acids in acidic pre-treatment on reducing sugar yield were studied. Results showed that the mixture of dilute sulfuric acid and MgSO4 exhibited a higher sugar yield than dilute acid. Among all pre-treatments used, the enzymatic treatment with thermostable enzymes showed the highest recovery of 0.951 g extracted glucose/g total sugar. Moreover, the enzymatic pre-treatment of wet microalgae was compared with dried ones at identical operational conditions and dried biomass concentration of 50 g/l, similar sugar yields were achieved which would be advantageous to reduce the need for drying of the microalgae biomass. Fermentation of the acidic and enzymatic treated samples to ethanol using Saccharomyces cerevisiae showed yield of 0.38 and 0.46 g/g glucose, corresponding to 76% and 92% of the theoretical values, respectively. The obtained results revealed that bioethanol yield after enzymatic hydrolysis of mixed microalgae culture are higher than those of acid hydrolysis.